2020
DOI: 10.1002/srin.202000313
|View full text |Cite
|
Sign up to set email alerts
|

High‐Temperature Tensile Properties and Deformation Behavior of Three As‐Cast High‐Manganese Steels

Abstract: Herein, the high‐temperature tensile properties and deformation behavior of three as‐cast high‐manganese steels with various carbon contents (0.028, 0.28, and 0.64 wt%) are investigated using a combination of hot tensile tests and isothermal hot compression on a Gleeble‐3500 thermomechanical simulator with different temperatures and strain rates. The results indicate that the carbon content increase makes a greater number of Mn–C dipoles available for a short‐range ordering and increases in the peak stress and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…How to control AlN precipitation has not yet reached to a consistent conclusion. Liu et al [12][13][14][15] have carried out a series of basic research on the microstructure and high temperature mechanical properties of TWIP steel, and counted the evolution of stored dislocation density and deformation twins, as well as their respective contributions to the strengthening and the work hardening. Xin et al 16) found that the dominant stable inclusion changed from MnO to Al 2 O 3 /MnS, MnS, and AlN with the increase of Al content from 0.002 to 2.1 mass% in the Fe-16Mn-Al-0.6C alloys.…”
Section: Introductionmentioning
confidence: 99%
“…How to control AlN precipitation has not yet reached to a consistent conclusion. Liu et al [12][13][14][15] have carried out a series of basic research on the microstructure and high temperature mechanical properties of TWIP steel, and counted the evolution of stored dislocation density and deformation twins, as well as their respective contributions to the strengthening and the work hardening. Xin et al 16) found that the dominant stable inclusion changed from MnO to Al 2 O 3 /MnS, MnS, and AlN with the increase of Al content from 0.002 to 2.1 mass% in the Fe-16Mn-Al-0.6C alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Wan et al have established a physical constitutive model considering strain coupling for Fe–25Mn–10Al–1.46C [ 20 ]. Shen et al have investigated high-temperature tensile behavior of as-cast high-Mn steels through constitutive modeling using the Zener–Hollomon parameter [ 21 ]. However, most of the models have considered materials with specific chemical compositions.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of temperature, cooling rate, and strain rate on the high‐temperature ductility of alloys with 17 wt.‐% Mn and ≈0–9 wt.‐% Al has been investigated by Borman et al [ 33 ] Depending on governing mechanisms like segregation and precipitation there may be different trends for the parameter on their effect on ductility. The high‐temperature tensile properties of the three as‐cast high‐manganese steels with 21 wt.‐% Mn, 5–6 wt.‐% Al and 0.028, 0.28, and 0.64 wt.‐% C have been investigated by hot tensile and hot compression tests at different temperatures and strain rates by Shen et al [ 34 ] It was found that steels with a carbon content of 0.028 and 0.28 wt% have similar hot brittle temperature ranges, whereas the ductility of the steel improves with increasing temperatures for 0.64 wt.‐% C.…”
Section: Introductionmentioning
confidence: 99%